2017
DOI: 10.5937/ffr1701011h
|View full text |Cite
|
Sign up to set email alerts
|

Progress in vegetable proteins isolation techniques: A review

Abstract: Novel vegetable proteins, like those extracted from abundant raw materials (grass) or agri-food by-products and waste streams (oilseed meals), are expected to be used as replacers for animal-derived proteins, due to higher production efficiency, reduced life cycle environmental impact and possibility to meet consumers' dietary or cultural preferences. Although having a versatile functionality (emulsifying, foaming, gelling, texturizing agents), application of proteins is limited since their properties highly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 44 publications
0
21
0
1
Order By: Relevance
“…Several novel technologies have also been discovered for protein extraction. These methods increases the yield, functionality and production sustainability of protein [ 60 ]. Novel technologies include ultrasound assisted extraction, electro-activation technique, pressurized low polarity water extraction, pulse–electric field technique, high voltage electrical discharge and complete or limited enzymatic (proteases) hydrolysis-assisted extraction.…”
Section: Bioprocess Techniques To Obtain Functional Flaxseed Ingrementioning
confidence: 99%
See 2 more Smart Citations
“…Several novel technologies have also been discovered for protein extraction. These methods increases the yield, functionality and production sustainability of protein [ 60 ]. Novel technologies include ultrasound assisted extraction, electro-activation technique, pressurized low polarity water extraction, pulse–electric field technique, high voltage electrical discharge and complete or limited enzymatic (proteases) hydrolysis-assisted extraction.…”
Section: Bioprocess Techniques To Obtain Functional Flaxseed Ingrementioning
confidence: 99%
“…Micellization, as an isolation technique helps in the preservation of native state of protein and removal of non–protein components [ 60 ]. Protein precipitate by ‘salting out’ at different salt concentrations.…”
Section: Bioprocess Techniques To Obtain Functional Flaxseed Ingrementioning
confidence: 99%
See 1 more Smart Citation
“…Soy Protein, hydrolyzed proteins (wheat gluten, wheat gliadin), zein, polypeptides -Alkaline extraction followed by protein precipitation at isoelectric pH; -protein extraction with salt solution, followed by precipitation from a salt extract by ultrafiltration, diafiltration membranes or dilution in cold water (micellization) [29]; and -novel techniques, such as ultrasound assisted extraction, enzyme-assisted extraction in the form of proteases and/or carbohydrolases [29].…”
Section: Proteinsmentioning
confidence: 99%
“…During the food processing, the occurrence of biologicalspecific waste is inevitable. The disposal of food waste is difficult due to its biological instability, potentially pathogenic nature, high water content, potentially rapid autoxidation and very high enzymatic activity.High risk of environmental pollution caused by the uncontrolled release of food by-products has led to the necessity of reducing the amount of waste through development of various bioprocesses toconvert the starting material tonovel food products.Numerous recent studies have shown that food industry by-products represent rich source of proteins and other nutraceuticals (Hadnađev et al, 2017;Rodrigues et al, 2012).…”
Section: Introductionmentioning
confidence: 99%